The D2 Dopamine Receptor Interferes With the Protective Effect of the A2A Adenosine Receptor on TDP-43 Mislocalization in Experimental Models of Motor Neuron Degeneration - Lai, Chia-You; Liu, Yu-Ju; Lai, Hsing-Lin; Chen, Hui-Mei; Kuo, Hung-Chi; Liao, Yu-Ping; Chern, Yijuang (Frontiers in Neuroscience, 2018)
The A2A adenosine receptor (A2AR) and D2 dopamine receptor (D2R) are two G-protein-coupled receptors that can form dimers and negatively regulate their partners. TAR DNA-binding protein (TDP-43) is a nuclear protein that has been implicated in amyotrophic lateral sclerosis (ALS). Mislocalization of TDP-43 from the nucleus to the cytoplasm is an early step of TDP-43 proteinopathy. Our previous studies indicated that A2AR is a potential drug target for ALS because treatment with an A2AR agonist (JMF1907; a T1-11 analog) prevents reactive oxygen species (ROS)-induced TDP-43 mislocalization in a motor neuron cell line (NSC34) and delays motor impairment in a TDP-43 transgenic ALS mouse model. Here, we set out to assess whether activation of D2R interferes with the beneficial effects of an A2AR agonist on motor neurons. We first demonstrated that A2AR and D2R are both located in motor neurons of mouse and human spinal cords and human iPSC-derived motor neurons. Expression of A2AR and D2R in NSC34 cells led to dimer formation without affecting the binding affinity of A2AR toward T1-11. Importantly, activation of D2R reduced T1-11-mediated activation of cAMP/PKA signaling and subsequent inhibition of TDP-43 mislocalization in NSC34 cells. Treatment with quinpirole (a D2 agonist) blunted the rescuing effect of T1-11 on TDP-43 mislocalization and impaired grip strength in a mouse model of ALS. Our findings suggest that D2R activation may limit the beneficial responses of an A2AR agonist in motor neurons and may have an important role in ALS pathogenesis.